Online Health Information Use, Assessment, and Gaps Identified by Minnesotans. Issue 4 (2nd October 2018) - Theis-Mahon, Nicole; Hunt, Shanda; Forbes, Nora
Abstract: This study identified where Minnesotans find online health information, how they use it, their confidence in assessing it, and what they think is missing. In August 2016, the University of Minnesota Health Sciences Libraries conducted a study of adults at the Minnesota State Fair. Convenience sampling yielded a total of 255 participants, with the majority being white, female, urban, and highly educated. Participants valued the ability to access OHI and used it for a variety of purposes. A high percentage of participants thought they had the knowledge, skills, and confidence to navigate OHI, yet were uncertain about indicators of quality.